Long‐term outcome of ovarian function in women with intermittent premature ovarian insufficiency. (14th June 2016) - Bachelot, Anne; Nicolas, Carole; Bidet, Maud; Dulon, Jérôme; Leban, Monique; Golmard, Jean Louis; Polak, Michel; Touraine, Philippe
Summary: Context: Spontaneous resumption of ovarian function is not a rare phenomenon in patients with premature ovarian insufficiency (POI). The outcome of this resumption is not known. Objective: To describe the outcome following the resumption of ovarian function in POI patients. Design: Cross‐sectional study. Setting: University medical centre. Patients and main outcome measures: Cumulative incidence of ovarian function resumption and risk factors arresting this resumption during follow‐up were determined in a large cohort of POI women. Results: Five hundred and seven patients were included in the study, with a follow‐up of 3·44 ± 4·05 years (0–29). Of these, 117 (23%) had features of ovarian function resumption. The cumulative incidence of pregnancy was 3·5% among the whole cohort and 15·3% among patients with resumption of ovarian function. Fifty‐five patients (47%) experienced an arrest of their resumption during the follow‐up period. In univariate analysis, high FSH and DHEA levels at initial evaluation were risk factors for the arrest of the resumption of ovarian function. In multivariate analysis, high FSH levels at the initial evaluation [1·89 (1·10–3·23), P = 0·03] and older age at diagnosis [1·53 (1·01–2·33), P = 0·04] were risk factors for the arrest of this resumption. Conclusion: Resumption of ovarian function is not a rare or brief phenomenon in POI women. The identification of predictive factors of this resumption, as well as its duration, increases our knowledge of the natural history of POI, and will improve the medical management, especially infertility counselling of these patients.